HERITAGE AND CULTURE-BASED EXPERIENTIAL TOURISM IN THE REPUBLIC OF ARMENIA։ NEEDS, PROBLEMS AND DEVELOPMENT PERSPECTIVES (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
Heritage and Culture-based Experiential Tourism (HCBET) development in the RA is discussed in this article, as well as its background, current situation, sectoral and territorial structure, and factors contributing to its development. This article identifies the major needs of this tourism and possible directions for development based on expert surveys and case studies of similar tourism companies. The article answers the following questions: what are the drivers of heritage and culture-based experiential tourism in the RA, and are there any specific needs that make this approach viable for sustainable tourism development in the RA? Culture tourism in Armenia can be traced back to the 1960s when Armenians living abroad visited their homeland to re-experience, enjoy, and interpret it. The visits consisted mainly of cognitive excursions to tangible historical and cultural monuments. Upon independence, the same image was preserved in the RA, but in recent decades, the country has started using its intangible cultural heritage for touristic purposes, laying the foundation for the development of HCBET. Based on the research, the following conclusions can be drawn: a) as a result of the investment programs of international organizations, HCBET is already developing in the RA; b) HCBET has developed mainly in the regions, especially in rural communities in the RA; c) a major component of HCBET is based on Armenian cuisine, arts, and crafts; d) HCBET does not yet have a widespread perception or interpretation in the RA; e) The RA has almost no public-private-educational/ scientific cooperation in HCBET; f) Several problems hinder the development of HCBET, including service quality problems in enterprises, low qualification of human resources, imperfect legal regulations (within the framework of standardization-licensing), low or no cooperation between enterprises, and the lack of inclusion of these tourism offers in tour packages offered by tour operators; g) There is a lack of educational programs on HCBET in the universities of the RA; h) people involved in HCBET need specialized training; i) Marketing strategies for HCBET companies need to be improved.
Keywords: culture; tourism; experiences; experiential tourism; sustainable tourism; Republic of Armenia